Pengaruh Pengungkapan Corporate Social Responsibility, Profitabilitas, Ukuran Perusahaan, dan Capital Intensity terhadap Agresivitas Pajak - Julius Sirait; Mira Kartika Dewi Djunaedi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The research aims to the effect of corporate social responsibility, profitability, firm size, and capital intensity on tax aggressiveness.The research method is quzntitative research. The data used were obtained from the financial statements on the Indonesia Stock Exchange during the research period. The population of this research are mining sector companies listed on the Indonesia Stock Exchange for period 2017-2020, which amounted to 48 companies. The sample in this research were 28 companies obtained using purposive sampling. The data analysis technique used is descriptive analysis. The result of this research showed that corporate social reasponsibility (CSR) has a negative and not significant effect on tax aggressiveness. Profitability (ROA) has a negative and not significant effect on tax aggressiveness. Firm size (SIZE) has a negative and not significant effect on tax aggressiveness. Capital intensity (CAPN) has a negative and not significant effect on tax aggressiveness.